Occurrence of Multidrug-Resistant Listeria monocytogenes in Environmental Waters: A Menace of Environmental and Public Health Concern - Kayode, Adeoye John; Semerjian, Lucy; Osaili, Tareq; Olapade, Ola; Okoh, Anthony Ifeanyi (Frontiers in Environmental Science, 2021)
The occurrence and antibiogram profiles of Listeria monocytogenes (Lm) in environmental waters in the Eastern Cape Province, South Africa were investigated. Seventy-eight samples from rivers, wastewater, and irrigation water were collected at different geographical locations within the province from February and September 2019. The procedure of the International Organization for Standardization EN ISO 11290:2017 part 1 and 2 was adopted for the isolation of Lm. The counts of presumptive Lm ranged from 2.0 × 103 CFU/100ml to 3.6 × 105 CFU/100ml. About 39.74 % of the samples were positive for Lm, and the isolates were confirmed as serotype 1/2a (78.95 %) and serotype 4b (21.05 %). About 68.42 % of the isolates demonstrated biofilm-forming potentials. Ten virulence determinants including the plcA, inlA, inlB were detected in all the isolates, however; inlC (85.97 %), inlJ (80.70 %), actA (59.65 %), prfA (92.98 %), plcB (89.47 %), hly (80.70 %) and mpl (73.68 %) were less prevalent. The antibiogram profiles of confirmed Lm isolates revealed high susceptibilities (> 50 %) to all antibiotics ranging from 52.63 % (cefotetan) to 100 % (ampicillin) except for sulfamethoxazole (35.09 %), erythromycin (26.32 %) streptomycin (38.60 %), oxytetracycline (45.61 %) and amoxicillin (49.12 %). Conversely, high resistance rates against sulfamethoxazole (63.16 %), oxytetracycline (54.39 %), amoxicillin (50.88 %) was observed. Isolates exhibited 52 resistance patterns against 22 antibiotics tested ranging from 1 to 15 antibiotics and 82.46 % show multidrug-resistance phenotypes against the antibiotics. The Antibiotic Resistance Index (ARI) of river water (0.18) is less than the permissible (0.2) Krumperman threshold, whereas that of irrigation and wastewater are higher than the Krumperman threshold. The (M)ARI of each of the isolate ranged from 0.05-0.68. Resistance determinants (21) encoding resistance against sulphonamides, β-lactamase, phenicols, aminoglycosides and tetracyclines were detected among the phenotypically resistant Lm isolates investigated which justifies the phenotypic resistance observed in this study. The abundance of resistance determinants in Lm recovered from environmental waters in this study suggests that the aquatic environments may serve as a channel for the dissemination of antimicrobial resistant Lm to other niches including the food chain.